The Nuclear Problem of the Korean Peninsula: Is There a Way of Ending the Deadlock? - V. Denisov (Международная аналитика)
The nuclear problem of the Korean peninsula remains unsolved, tensions continuing for the past five years. The mechanism of the Six-Party Talks in which Russia, China, the USA, Japan, North and South Korea took part, is inactive, while each party develops its own strategy to counteract the new nuclear program of North Korea. Such an approach stimulates further escalation in the region, because there is no mutual understanding of North Korea nuclear status. In addition there exist a number of contradictions between the members of Six-Party Talks, each of them trying to resolve North Korean issue pursuing their own interests. However, in the current situation a peaceful resolution of the problem is still possible. Moreover, it is the only reasonable solution.